The influence of mono ethylene glycol (MEG) on CO2 corrosion of carbon steel at elevated temperature (80 to 120°c) - Pojtanabuntoeng, Kod; Salasi, Mobin; Gubner, Rolf (National Assoc. of Corrosion Engineers International, 2014)
Monoethylene glycol (MEG) is injected in the pipelines to prevent hydrate formation, and subsequent pipeline blockage. Recent investigations indicated that presence of MEG could impede CO2 corrosion of carbon steel, although many aspects remain unknown. In the current study, experiments were conducted at 80 oC (176 oF), atmospheric pressure, and 100 oC (212 oF), and 120 oC (248 oF) at pCO2 of 10 bar. Test solutions had different ratios of MEG/Ultra-pure water with 3 wt. % NaCl concentration. Electrochemical techniques such as linear polarization resistance (LPR), Electrochemical Impedance Spectroscopy (EIS) and Tafel polarization were employed to investigate the corrosion rate and phenomenon. Corroded surface of the samples were characterized using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) techniques. This research aims to provide an improved insight on contribution of MEG on CO2 corrosion of carbon steel, at elevated temperatures.